Effect of roadway environment characteristics on pedestrian safety at signalised intersections in Amman - Eman A. Shehadeh; Ali H. Al-Bayatti; Muhammed Ali Bingöl (Urban, Planning and Transport Research, 2024)
Pedestrian safety becoming a serious issue, especially in developing nations, wherein higher crash rates have been reported by the World Health Organization. Despite evidence suggesting higher pedestrian crash counts at signalised intersections in urban areas, there is a lack of in-depth analysis in most developing countries. Motivated by this need, this study aims to: 1) identify significant roadway environment characteristics and traffic volume factors influencing pedestrian – vehicle accidents at signalised intersections in Amman, Jordan, 2) elucidate relationships between pedestrian – vehicle accidents and these factors, and 3) discuss the limitations of pedestrian crash data and propose solutions for future research. We have analysed 166 accidents at 47 signalised intersections in Amman during the period of 2007–2019. The multilevel Generalised Linear Mixed Gamma regression model is the best fit for the data, indicating significant positive correlations between pedestrian crash frequencies and Annual Average Daily Traffic, pedestrian crossing volume, number of lanes, average lane width, and number of parking sides. Conversely, commercial land use and the presence of public transit facilities showed significant negative correlations with pedestrian crashes. This work presents a novel approach that will help developing countries to determine and explain pedestrian crash causes while considering various challenges in these contexts.